Variation in the Level of Thyroid Markers in Association with Inflammation in Patients with Type 2 Diabetes - Siddiqui, Khalid; George, Teena P.; Joy, Salini S.; Mujammami, Muhammad (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: A possible relationship between thyroid hormones and glucose metabolism in diabetes has already been established. Objectives: We aimed to evaluate the thyroid function markers and their relationship with inflammation, which is considered as a pathogenic condition of diabetes. Methods: This cross-sectional study included 276 patients with type 2 diabetes. Serum levels of thyroid (TSH, FT4, and FT3) and inflammatory markers (CRP, IL-6, and TNF-α) were measured. Results: The mean age of the subjects was 55.2 years and mean diabetes duration of 16.8 years. The inflammatory markers showed significant differences with the tertiles of TSH and thyroid hormones. TSH was significantly correlated with inflammatory markers, IL-6 (r = 0.13, P = 0.020) and TNF-α (r = 0.17, P = 0.003), while FT4 had a correlation only with TNF-α (r = 0.25, P = <0.001). FT3 was negatively correlated with inflammatory marker IL-6 (r = -0.14, P = 0.020), HbA1c (r = -0.12, P = 0 .040), and HOMA-IR (r = -0.17, P = 0.010). Conclusion: Abnormalities in the thyroid hormone metabolism are related to the increased inflammatory activity as well as insulin resistance, and are associated with the disorders of glucose metabolism.
Keywords: thyroid hormones